Customer satisfaction and brand switching intention of mobile service among university students / Mei Ling Goh ...[et al.] - Mei, Ling Goh; Seng, Huat Tan; Ang, Elaine Hwee Chin; Mei, Qi Yap (Universiti Teknologi MARA, Shah Alam: Accounting Research Institute (ARI), 2020)
The significant role of telecommunication technology in the economic sector has caused increasing competition in the mobile service market. As for business survival, a mobile service package is now required to become even more innovative than before. Customer satisfaction plays a vital role in mobile services and it will impact on brand switching among mobile service users. This study aimed to examine factors that influence customer satisfaction which will subsequently affect the brand switching intention of customers. Among the factors studied were service quality, service pricing, customer service and value-added service. A total of 200 students from a local private university were recruited using the convenience sampling thechnique based on self-administered questionnaires. The collected data was then analysed using PLS-SEM. The findings show that all the factors tested were found to have a positive impact on customer satisfaction except service quality and value added service. Customer satisfaction was also found to have a negative effect on brand switching of customers of mobile service. The findings of this research have provided useful information to mobile service providers in planning their marketing strategy. They have to be more innovative in their efforts to meet the growing and different needs of customers and retain them from switching to opponent mobile service brands in the market.